Target distance measurement method using monocular vision. Issue 13 (2nd October 2020) - Jiafa, Mao; Wei, Huang; Weiguo, Sheng
Abstract : Most existing machine vision‐based location methods mainly focus on the spatial positioning schemes using one or two cameras along with non‐vision sensors. To achieve an accurate location, both schemes require processing a large amount of data. In this study, the authors propose a novel method, which requires much less amount of data to be processed for measuring target distance using monocular vision. Based on the geometric model of camera imaging, the parameters of the camera (such as camera's focal length and equivalent focal length.), as well as the principle of analogue signal being transformed into a digital signal, the authors derive the relationship among the target distance, field of view, equivalent focal length and camera resolution. Experimental results show that the proposed method can effectively and accurately achieve the target distance measurement.